Interannual variability of NDVI and species richness in Kenya - Oindo, B. O.; Skidmore, A. K. (International journal of remote sensing, 2002)
Ecologists have long recognized the spatial variability of species richness. In an attempt to identify the factors responsible for this variability, ecologists have traditionally used environmental data obtained from sparse point samples (such as meteorological stations). However, remotely sensed data also provide a means of estimating relevant environmental factors and thereby improving predictions of species richness. The Advanced Very High Resolution Radiometer Normalized Difference Vegetation Index (AVHRR NDVI) has been shown to be related to net primary productivity (NPP) and actual evapotranspiration (AET) for many vegetation types. NPP and AET have frequently been used as surrogate measures for species richness. Local spatial variability of NPP and AET, indicating habitat heterogeneity, is hypothesized as another influence on species richness. We examined the relationship between interannual maximum NDVI parameters and species richness of vascular plants and mammals. The study was done at a landscape scale, which matches the scale of data collection. Statistical analyses revealed that higher average NDVI results in lower species richness, whereas standard deviation and coefficient of variation correlated positively with species richness. Thus, NDVI parameters appear to represent environmental factors influencing species richness. Hence, by utilizing remote sensing, our understanding of the spatial variability of species richness was improved.